A new species of Oecleus (Hemiptera: Auchenorrhyncha: Fulgoromorpha: Cixiidae) from the Osa Peninsula in Costa Rica - Echavarria, Marco A. Zumbado; Barrantes, Edwin A. Barrantes; Bartlett, Charles R.; Helmick, Ericka E.; Bahder, Brian W. (Zootaxa, 2023)
Recent palm survey work in Costa Rica focusing on planthoppers has resulted in the discovery of several new taxa, primarily in Cixiidae and Derbidae. In addition to sampling palms directly, light trapping has been utilized to collect a broader range of planthoppers that may not be found on palms. During a light trapping event at the Cotinga Biological station on the Osa peninsula in Costa Rica, a cixiid was collected and subsequently determined to be an unidentified species in the genus Oecleus Stål. Herein, the novel taxon, Oecleus urru sp. n., is described. Supplemental molecular data for the barcoding region (5’ half) of the cytochrome c oxidase subunit I (COI) gene, 18S rRNA gene, and histone 3 (H3) gene is provided to support the placement of the novel taxon in the genus Oecleus.